Coma with miosis and bradycardia. - Porfírio, H; Matos, L D (Acta Médica Portuguesa, 1994)
The authors report a clinical case of clonidine poisoning in a 20-month-old child. Although a paradigmatic case, due to extensive symptomatology, it presented a diagnostic and therapeutic challenge.